The blue guide to Indiana - Martone, Michael (FC2, 2001)
The master of the nearly true is back with The Blue Guide to Indiana, an ersatz travel book for the Hoosier State. Michael Martone, whose trademark is the blurring of the lines between fact and fiction, has created an Indiana that almost is, a landscape marked by Lover's Lane franchises and pharmaceutical drug theme parks. Visit the Trans-Indiana Mayonnaise Pipeline and the Field of Lightbulbs. Learn about Our Lady of the Big Hair and Feet or the history of the License Plate Insurrection of 1979. Let Martone guide you through every inch of the amazing state that is home to the Hoos.